'Don't show that you're scared': resilience in providing healthcare in a UK low-to-medium secure hospital. Issue 1 (1st January 2021) - Husted, Margaret; Dalton, Rheyanne
ABSTRACT: Background: Healthcare provision within specialist hospitals is associated with heightened levels of stress and burnout, risking negative implications for employees, organisations, and patients. Minimal research has focused on lower-skilled worker experiences. This study explores frontline care workers' experience and perceptions of providing care within a low-to-medium secure hospital within the UK. Method: Eight semi-structured interviews were conducted with healthcare assistants and mental health nurses (18–65 years) at a low-to-medium secure hospital. Thematic analysis (Braun & Clarke, 2006) was used to analyse the data. Results: Three main themes are proposed: 'Resilience to threat' capturing the daily occurrence and normalisation of threat; 'Need for support' shows peer to peer talk as the primary coping mechanism but importantly, a possible disconnect between perceptions, and provision, of organisational support; finally, 'Unique environment' highlights the dual aspect of providing care and correction whilst coping with common challenges e.g. staff shortages. Conclusions: Results provide insight into the pressures experienced by frontline healthcare workers alongside staff motivation to 'make a difference'. Findings highlight some unique challenges of working in low-to-medium secure hospitals which contributes to negative outcomes for worker engagement, performance, and individuals' mental and physical health. Implications for organisations and future practice are discussed.